PENERAPAN KEBIJAKAN IZIN PEMANFAATAN AIR DAN ENERGI AIR DI TAMAN NASIONAL KERINCI SEBLAT DALAM MEWUJUDKAN PEMBANGUNAN BERWAWASAN LINGKUNGAN - Arif Wibowo; I Gusti Ayu Ketut Rachmi Handayani; Al. Sentot Sudarwanto (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
ABSTRACTThis paper aims to find out and analyze the implementation of regulation of water and water energy utilization in national park especially in Kerinci Seblat National Park. The implementation of the ministry regulation can be defined as an achievement of purposes, values and directed practices. This research uses the research method of empirical law or non-doctrinal in conducting the implementation towards the permit regulation of water and water energy utilization in National Park. The case study is conducted in the Great Hall of Kerinci Seblat National Park. In implementing the permit, the permit policy of water and water energy utilization has been conducted accordance with the regulation as well as the permit granting has been done thoroughly and calculated the enviromental needs. There are some obstacles faced in implementing the permit, so it needs synchronization with the related regulations, socialization, coordination among the local governments. In additional, it also needs clear timetable in the process of administrative and technical consideration as well as it needs evaluation monitoring and coaching to make the function of permit appropriate as the control and arrangement in the term of technical and legal certainty. The activities should observe the environmental impact and support the efforts in improving the society’s prosperity and the quality of human life as well as realizing the environmental-based development.Key words: The policy implementation; The Permit Regulation of Water and Water Energy Utilization; National Park; Environmental-based Development.Artikel ini bertujuan untuk mengkaji dan menganalisis penerapan kebijakan izin pemanfaatan air dan energi air di taman nasional khusunya Taman Nasional Kerinci Seblat. Penerapan peraturan menteri tersebut dapat diartikan sebagai suatu pencapaian tujuan, nilai-nilai dan praktek-praktek yang terarah. Penelitian ini mengunakan metode penelitian hukum empiris atau non doktrinal dengan analisis data kualitatif dengan model interaktif, lokasi penelitian di Balai Besar Taman Nasional Kerinci Seblat. Dalam penerapan kebijakan izin pemanfaatan air dan energi air telah dilaksanakan sesuai dengan peraturan perundang-undangan, pemberian izin dilakukan dengan cermat dan memperhitungkan kepentingan lingkungan. Dalam pelaksanaan anya adanya kendala untuk itu, perlunya singkronisasi peraturan yang terkait, sosialisasi peraturan, upaya peningkatan koordiansi dengan pemerintah daerah, dan perlunya pengaturan tata waktu yang jelas dalam proses syarat administrasi dan pertimbangan teknis, serta perlunya pengawasan, evaluasi dan pembinaan agar sesuai fungsi perizinan sebagai penertib dan pengatur dilihat dari segi teknis dan kepastian hukum. Dalam kegiatan tersebut juga memperhatikan dampak lingkungan dan mendukung upaya peningkatan kesejahteraan masyarakat dan mutu kehidupan manusia serta mewujudkan pembangunan yang berwawasan lingkungan.Kata Kunci : Penerapan kebijakan; Izin Pemanfaatan Air dan Energi Air; Taman Nasional; Pembangunan berwawasan lingkungan